Determination Of Water Quality Depth For Stormwater Facilities In Peninsular Malaysia - Alang Othman, Mazlina (2018)
Urbanization increases the amount of pollution carried out to downstream waterways. Best Management Practises (BMPs) have been identified as an approach to solve the problems. The effectiveness of BMPs depends on the volume of storm runoff that can be captured and treated by them, which is referred as water quality volume (WQV) and requires a fixed depth of runoff which is referred to as "Water Quality Depth" (WQD). The recommended WQD value for Malaysia stands at 40 mm and generated from limited data. This research aims to determine WQD by using local rainfall data and develop WQD distribution map for Peninsular Malaysia. It shows that 90th percentile is an optimum rainfall depth value for Northern and Central regions of Peninsular Malaysia while 95th percentile for Southern and East Coast regions. At 90th percentile, WQD was found to be in the range of 33 - 57 mm. However, WQD at 95th percentile was much higher which is in the range of 44 - 90 mm. Therefore, WQD of 40 mm was insufficient for Peninsular Malaysia and it is suggested that the WQD be reviewed. Findings of this study can be used for such a purpose. This study also shows that, due to the small number of significant increasing trends in extreme value identified, it was unnecessary to include extreme value in WQD estimation to avoid over design in BMPs facilities. For WQD distribution map, Inverse Distance Weighting (IDW) was chosen as the most reliable method for WQD interpolation at 90th percentile while Ordinary Kriging at 95th percentile. A field study at a constructed wetland was carried out to ascertain the relationship between WQD and BMPs facilities treatment performance. TSS recorded higher performance when rainfall depth was below than WQD value. However, BOD, COD, TN, TP and AN recorded higher performance when rainfall depth exceeded WQD value.